Study on the Hydration of α-Pinene Catalyzed by α-Hydroxycarboxylic Acid–Boric Acid Composite Catalysts - Zhonglei Meng; Rongxiu Qin; Rusi Wen; Guiqing Li; Zhongyun Liang; Junkang Xie; Zhangqi Yang; Yonghong Zhou (Molecules, 2023)
In this study, seven types of α-hydroxycarboxylic acids were selected to form composite catalysts with boric acid, and their catalytic properties were studied using the catalytic hydration of α-pinene. The results showed that the composite catalyst of boric acid and tartaric acid had the highest catalytic activity. With an α-pinene, water, acetic acid, tartaric acid, and boric acid mass ratio of 10:10:25:0.5:0.4, the reaction temperature was 60 °C, the reaction time was 24 h, the conversion of α-pinene was 96.1%, and the selectivity of terpineol was 58.7%. The composite catalyst composed of boric acid and mandelic acid directly catalyzed the hydration of α-pinene in the absence of a solvent. Under the optimal conditions, the conversion of α-pinene reached 96.1%, and the selectivity of terpineol was 55.5%. When the composite catalyst catalyzed α-pinene to synthesize terpineol in one step, the terpineol was optically active, and terpineol synthesized using the two-step method with the dehydration of p-menthane-1,8-diol monohydrate was racemic. These composite catalysts may offer good application prospects in the synthesis of terpineol.